Reimagining history in contemporary Spanish media : theater, cinema, television, streaming - Smith, Paul Julian (Visual culture (Cambridge, England), 2021)
"The aim of this book is to explore the field of visual culture within contemporary Spanish studies in the specific case of the reimagining of past history for present audiences"--Introduction